Pengaruh Kualitas Pelayanan, Harga Dan Ketepatan Waktu Terhadap Kepuasan Konsumen Di Rere Jaya Jeans Kota Malang - Syaiful Anam; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to determine and analyze the influence of service quality, price and timeliness on consumer satisfaction at Rere Jaya Jeans Malang City. The population in this study are consumers who have used Rere Jaya Jeans products or services. The data collection method in this study used a questionnaire with a sample of 75 respondents. The independent variable in this study is the influence of service quality, price and punctuality and the dependent variable is consumer satisfaction. The analytical method used in this study is multiple linear regression analysis and processed using SPSS 16. The results of this study simultaneously show that the influence of service quality, price and punctuality has a positive and significant effect on consumer satisfaction. Partially, service quality, price and punctuality have a positive and significant effect on consumer satisfaction. Keywords: Service Quality, Price, Timeliness and Customer Satisfactio